2019
DOI: 10.1136/bmjsem-2018-000375
|View full text |Cite
|
Sign up to set email alerts
|

Return to play following anterior cruciate ligament reconstruction: incorporating fatigue into a return to play functional battery. Part A: treadmill running

Abstract: BackgroundThe risk of reinjury and other sequelae following anterior cruciate ligament reconstruction (ACLR) remains high. Lack of knowledge regarding factors contributing to these risks limits our ability to develop sensitive return to play (RTP) tests. Using a running task, we evaluate whether fatigue induces alterations in foot progression angle (FPA), a proposed biomechanical risk factor and could be used to enhance RTP test sensitivity.MethodTransverse plane foot kinematics (FPA) were assessed for 18 post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Other possible reasons for the higher risk of contralateral injuries include biomechanical changes or altered neuromuscular function after ACL reconstruction. 32 In a biomechanical analysis of patients who had undergone ACL reconstruction, Connell et al 4 found that during treadmill running, patients protected their reconstructed knee but consequently exposed the contralateral knee to greater internal rotation forces. Neuromuscular changes such as the H-reflex, quadriceps strength deficits, or changes related to donor site morbidity have been proposed as other potential risk factors for a contralateral ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible reasons for the higher risk of contralateral injuries include biomechanical changes or altered neuromuscular function after ACL reconstruction. 32 In a biomechanical analysis of patients who had undergone ACL reconstruction, Connell et al 4 found that during treadmill running, patients protected their reconstructed knee but consequently exposed the contralateral knee to greater internal rotation forces. Neuromuscular changes such as the H-reflex, quadriceps strength deficits, or changes related to donor site morbidity have been proposed as other potential risk factors for a contralateral ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…When making rehabilitative decisions on return to sport, it is important for clinicians to consider the postoperative changes to the biomechanics of the knee and the association between high activity levels and repeat ACL injury. 7,28,50 Although the ''perfect'' graft would have the lowest risk of ipsilateral reinjury, it would also have the highest rate of return to activity, potentially increasing the risk of injury to the contralateral ACL. Injury prevention programs are known to be effective in reducing ACL injury; however, further studies are required to evaluate the efficacy of postoperative prevention measures in reducing contralateral ACL injury, especially in patients with a patellar tendon graft.…”
Section: Time (Years)mentioning
confidence: 99%